2017
DOI: 10.1021/acsami.6b16111
|View full text |Cite
|
Sign up to set email alerts
|

Control of Surface and Edge Oxidation on Phosphorene

Abstract: Phosphorene is emerging as an important two-dimensional semiconductor, but controlling the surface chemistry of phosphorene remains a significant challenge. Here, we show that controlled oxidation of phosphorene determines the composition and spatial distribution of the resulting oxide. We used X-ray photoemission spectroscopy to measure the binding energy shifts that accompany oxidation. We interpreted these spectra by calculating the binding energy shift for 24 likely bonding configurations, including phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
191
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(211 citation statements)
references
References 77 publications
14
191
1
Order By: Relevance
“…Indeed, the presence of electronegative groups such as oxygen or hydroxide on the surface of bP withdraws charge leading to more tightly bound phosphorus electrons. As a result, PxOy species experience a higher binding energy for P 2p core electrons in comparison to un-oxidized material [36]. Thus, we determine an average thickness of phosphorus oxide of (13.9 ± 0.4) Å for pristine bP and of (6.2 ± 0.4) Å for Ni/2D bP after aging.…”
Section: X-ray Photoemission and Absorption Spectroscopy Studymentioning
confidence: 98%
“…Indeed, the presence of electronegative groups such as oxygen or hydroxide on the surface of bP withdraws charge leading to more tightly bound phosphorus electrons. As a result, PxOy species experience a higher binding energy for P 2p core electrons in comparison to un-oxidized material [36]. Thus, we determine an average thickness of phosphorus oxide of (13.9 ± 0.4) Å for pristine bP and of (6.2 ± 0.4) Å for Ni/2D bP after aging.…”
Section: X-ray Photoemission and Absorption Spectroscopy Studymentioning
confidence: 98%
“…Other studies have demonstrated the stability of this oxide in both a stoichiometric and nonstoichiometric configuration, with a direct gap tuning by means of crystal strain and electric fields . These theoretical studies will contribute to achieving technological applications for phosphorene oxide, among which there are gas sensing and gas catalysis, as well as possible humidity detection . The oxidation of the BP could favor the use of this material as a gas sensor or in other opto‐electronic applications.…”
Section: Introductionmentioning
confidence: 88%
“…Due in part to monolayer's unique electronic properties, in particular, its high surface/volume ratio. It is also possible to manipulate the electronic properties in these materials using functionalization, whether it is by doping, the presence of structural defects, or by creating heterostructures that combine monolayers of different chemical compositions …”
Section: Introductionmentioning
confidence: 99%
“…[40,43,49] Moreover, the edges and steps undergo rapid degradation in few-layered samples, where the role of vacancy defects is understandably negligible. [44,46] It is also observed that the oxidation rate increases with the reduction in the number of layers, [41,45] which indicates a stronger interaction of oxygen at the surface. Formation energies E f of the SV(5|9) and SV(55|66) defects at the apical layer with varied layer thickness.…”
Section: Introductionmentioning
confidence: 95%
“…Although the exact mechanism continues to be investigated, it is understood that the strong chemical bonding between lone pair electrons of phosphorus and π * electrons of oxygen initiate the chemical degradation. [40][41][42][43][44][45][46][47][48][49] Further, degradation is accelerated as the hydrophilicity of phosphorene increases with oxidation. [40,43,49] Moreover, the edges and steps undergo rapid degradation in few-layered samples, where the role of vacancy defects is understandably negligible.…”
Section: Introductionmentioning
confidence: 99%